2021
DOI: 10.2174/1874944502114010425
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Experiences of Participating in PMTCT Option B Plus: An Explorative Study on HIV-positive Pregnant Women in Eswatini

Abstract: Background: Eswatini has adopted the PMTCT Option B+ approach as a strategy for the prevention of mother-to-child transmission of HIV. Objective: This study aimed to explore how pregnant Swazi women perceived and experienced PMTCT Option B+ and examined challenges they faced in disclosing their HIV status to their male partners. Methods: We interviewed 15 HIV-positive pregnant women selected using purposeful sampling from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Moreover, some participants who had accepted the HIV test and treatment initiation felt that despite the strategy being a good strategy that does not waste time, it was coercive in nature, and that not enough time or space was given to them to decide whether or not to take treatment. This is consistent with other studies where the participants felt coerced to test and treat and felt that they were not given enough time to decide [3,7].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, some participants who had accepted the HIV test and treatment initiation felt that despite the strategy being a good strategy that does not waste time, it was coercive in nature, and that not enough time or space was given to them to decide whether or not to take treatment. This is consistent with other studies where the participants felt coerced to test and treat and felt that they were not given enough time to decide [3,7].…”
Section: Discussionsupporting
confidence: 90%
“…Professionalism, showing empathy, a caring attitude and dedicating enough time to counselling patients are key to facilitating ART initiation [7]. Studies on pregnant women also found that due to a good staff attitude and counselling, they were able to actively participate in the Prevention of Mother to Child Transmission (PMTCT) activities [3,7]. Moreover, a study by Adams et al [19] concurs that a supportive clinic environment promotes continuous adolescent engagement in HIV care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation